Enhancement of tracheal cartilage regeneration by local controlled release of stromal cell-derived factor 1α with gelatin hydrogels and systemic administration of high-mobility group box 1 peptide - Kumiko (Ogi) Suzuki; Tatsuya Okamoto; Katsuto Tamai; Yasuhiko Tabata; Etsuro Hatano (Regenerative Therapy)
Introduction: This present study evaluated the effect of combination therapy with stromal cell-derived factor 1α (SDF-1α) and high-mobility group box 1 (HMGB1) peptide on the regeneration of tracheal injury in a rat model. Methods: To improve this effect, SDF-1α was incorporated into a gelatin hydrogel, which was then applied to the damaged tracheal cartilage of rats for local release. Furthermore, HMGB1 peptide was repeatedly administered intravenously. Regeneration of damaged tracheal cartilage was evaluated in terms of cell recruitment. Results: Mesenchymal stem cells (MSC) with C-X-C motif chemokine receptor 4 (CXCR4) were mobilized more into the injured area, and consequently the fastest tracheal cartilage regeneration was observed in the combination therapy group eight weeks after injury. Conclusions: The present study demonstrated that combination therapy with gelatin hydrogel incorporating SDF-1α and HMGB1 peptide injected intravenously can enhance the recruitment of CXCR4-positive MSC, promoting the regeneration of damaged tracheal cartilage.